The Paradigm of Fiqh Muamalah Maliyah in the Halal Tourism Ecosystem: Integration of Maqashid Syariah and Sustainable Business Models - Dwi Vita Lestari Soehardi; Sri Sudiarti; Marliyah Marliyah (Brilliant International Journal Of Management And Tourism, 2025)
Halal tourism has become a rapidly growing sector of the global economy, driven by the increasing population of shariah-conscious Muslims and the demand for travel experiences that are in line with Islamic values. However, this growth demands a robust framework that not only ensures shariah compliance at the transactional level (fiqh muamalah maliyah), but also promotes social justice, environmental sustainability, and long-term economic resilience. This article presents a new paradigm that deeply integrates maqashid shariah (the highest objectives of shariah) with sustainable business models in the halal tourism ecosystem. Using a critical literature analysis approach and conceptual study, this article examines how the core principles of Islamic jurisprudence such as the prohibition of riba, gharar (uncertainty), maysir (gambling), justice ('adl), transparency, and social responsibility (maslahah) can serve as the foundation for building an authentic and sustainable halal tourism business model. The article argues that the integration of maqasid shariah (especially the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-'aql), progeny (hifz al-nasl), and property (hifz al-mal)) not only strengthens shariah compliance but also creates significant added value through increased brand trust, consumer loyalty, better risk management, responsible innovation, and contribution to the Sustainable Development Goals (SDGs). Case studies and best practices from various destinations are illustrated to demonstrate the practical application of this paradigm. This article concludes that the holistic integration of fiqh muamalah maliyah, maqashid shariah, and sustainable business principles is essential not only for the religious legitimacy of halal tourism, but also for its competitive sustainability and meaningful contribution to the well-being of humanity and the planet.